Unprecedented Formation of 2, 5‐Diaminoquinones from the Reaction of Vanillin with Secondary Amines in Aerobic Conditions. Issue 1 (20th December 2019) - Barbero, Mauro; Papillo, Valentina A.; Grolla, Ambra A.; Negri, Roberto; Travaglia, Fabiano; Bordiga, Matteo; Condorelli, Fabrizio; Arlorio, Marco; Giovenzana, Giovanni B.
Abstract : Vanillin is widely used as a flavoring agent in foods, perfumes and in several other applications. Even if huge amounts of vanillin are annually employed in these manufacturing processes, its reactivity is underexplored, especially for the formation of potentially toxic substances. In this context, we observed the formation of orange to red crystalline compounds in the reaction of vanillin with secondary amines in aerobic conditions. NMR and HRMS allowed identifying the products as 2, 5‐diamino‐1, 4‐benzoquinones. Preliminary investigations of this reaction led to a proposed mechanism involving an oxidative fragmentation of vanillin as the key step. MTT tests did not show any toxic effect up to 0.1 mm . Abstract : The Colour of the Flavour: Vanillin reacts with secondary amines in aerobic conditions to give highly colored 2, 5‐diamino‐1, 4‐benzoquinones. This unprecedented transformation is potentially operative during food processing. MTT tests dismiss toxicity concerns on the products even at 0.1 mm .